Research on the deformation control of surrounding rock about large-section tunnel in strong-medium weathered slate - Niu, Zelin; Wang, Yaqiong; Fan, Shengyuan (Frontiers in Earth Science, 2023)
Affected by dip angle and thickness of strata and the tunneling method, soft rock tunnel has obvious characteristics of large deformation, long deformation time and difficult support. Based on a case study of Gelong Tunnels, the deformation and failure mechanism of surrounding rock, stress characteristics of supporting structural and control method of large section highway tunnel passing through strong-medium weathered carbonaceous slate stratum are studied,and this paper proposed the Comprehensive reinforcement CD construction method based on strengthening the longitudinal stiffness of supporting structure and increasing the integrity of surrounding rock. The results showed that the deformation of surrounding rock and the stress of supporting structure increased rapidly in the early stage of construction. The cumulative deformation of vault settlement and horizontal convergence reached 116.9 mm and 97.9 mm, respectively, accounting for 73.53 % and 76.62 % of the total deformation. The proportion of surrounding rock pressure shared by the primary support and the secondary lining was about 8.9:1.1.This shows that the initial support after comprehensive reinforcement has a strong supporting capacity, and effectively reduces the secondary lining pressure of the tunnel, which plays a vital role in the long-term service of the secondary lining.